2015
DOI: 10.1080/09168451.2014.972325
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion properties of Lactobacillus rhamnosus mucus-binding factor to mucin and extracellular matrix proteins

Abstract: We previously described potential probiotic Lactobacillus rhamnosus strains, isolated from fermented mare milk produced in Sumbawa Island, Indonesia, which showed high adhesion to porcine colonic mucin (PCM) and extracellular matrix (ECM) proteins. Recently, mucus-binding factor (MBF) was found in the GG strain of L. rhamnosus as a mucin-binding protein. In this study, we assessed the ability of recombinant MBF protein from the FSMM22 strain, one of the isolates of L. rhamnosus from fermented Sumbawa mare milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 41 publications
1
27
0
1
Order By: Relevance
“…Moreover, GST‐APF1 bound tightly to fibronectin and exhibited a K D value of 68.7 nM. Previous studies have shown high affinity to fibronectin of the S‐layer protein SlpA from L. brevis ATCC 8287 ( K D = 89.8 nM) (de Leeuw et al ., ), and of the mucus‐binding factor from L. rhamnosus FSMM22 ( K D = 190 nM) (Nishiyama et al ., ). Our findings suggest that APF1 may belong to a class of Lactobacillus adhesins that exhibit high affinity for fibronectin.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, GST‐APF1 bound tightly to fibronectin and exhibited a K D value of 68.7 nM. Previous studies have shown high affinity to fibronectin of the S‐layer protein SlpA from L. brevis ATCC 8287 ( K D = 89.8 nM) (de Leeuw et al ., ), and of the mucus‐binding factor from L. rhamnosus FSMM22 ( K D = 190 nM) (Nishiyama et al ., ). Our findings suggest that APF1 may belong to a class of Lactobacillus adhesins that exhibit high affinity for fibronectin.…”
Section: Discussionmentioning
confidence: 97%
“…A similar interaction has been observed for the S‐layer protein CbsA from L. crispatus JCM 5810, which binds laminin, collagens and lipoteichoic acids (Antikainen et al ., ). Other studies have demonstrated the affinity of glutamine synthetase and glucose‐6‐phosphate isomerase from L. crispatus ST1 to laminin, collagen I and fibronectin (Kainulainen et al ., ), and that of mucus‐binding factor from L. rhamnosus strains GG and FSMM22 to laminin, collagen IV, fibronectin and mucin (Nishiyama et al ., ). Bacterial adhesion has been suggested to depend on cell surface hydrophobicity and/or electric charge (Schär‐Zammaretti et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Methodologies to screen for bacterial adhesion to mucins have previously employed thin layer chromatography overlay [26], enzyme-linked immunosorbent assay [15], micro-titre plate assays [8,25,27], surface plasmon resonance [16,28,29,30,31], fluorescence spectroscopy [20], mucin microarrays [32], flow cytometry [33], and cell-based assays [26,34,35,36]. However, due to the complexity and diversity of mucin glycosylation, these methods typically provide qualitative binding data indicating only presence or absence of interaction.…”
Section: Introductionmentioning
confidence: 99%
“…rhamnosus FSMM22 (Nishiyama et al . ). Two surface layer proteins are known Fn‐binding proteins: SlpA of Lactobacillus brevis ATCC 8287 (Hynönen et al .…”
Section: Introductionmentioning
confidence: 97%